Pemberdayaan Masyarakat melalui Program Lumbung Pangan Padi Organik: Studi Kasus di Kelompok Tani Sari Alam Desa Cibatu Kecamatan Cikembar Kabupaten Sukabumi - Dede Deri Efendi; Ema Hilma Meilani; Ashrul Tsani (Jurnal Surya, 2022)
Empowerment is an effort to build potential by motivating and raising awareness, the purpose of empowerment to create social change in the community. A society is a large number of people who live within the same territory and form a group. Farmer groups are a form of social because they can be used as a place for teaching and learning. Sari Alam farmer group is an agricultural institution with the aim of developing skills in organic rice cultivation. This study aims to describe the process of empowerment and income comparison before and after receiving the organic rice cultivation food barn program in the Sari Alam farmer group. The research method used is a descriptive method of survey type. Data collection in this study is primary and secondary data. The sampling technique used is Purposive sampling. The design of the analysis uses descriptive with average retrieval and revenue analysis. The results of the community empowerment research aim to increase the capacity and quality of farmers to grow and develop into empowered, independent and prosperous farmers in terms of the comparison of income results in rice cultivation.